EFFECT OF THE SEAFLOOR TOPOGRAPHY TO GRAVITY ANOMALY IN THE EAST VIETNAM SEA AND ADJACENT AREAS - Dung, Tran Tuan; Minh, Nguyen Quang; Anh, Vu Thu (Vietnam Journal of Marine Science and Technology, 2012)
Gravity terrain correction of seafloor topography is very necessary and decisive for effective in interpretation of marine gravity data. In this study, gravity terrain correction is calculated in combination with the methods that given by Nagy (1966) and Kane (1962). A digital terrain model of the seafloor topography (DEM) 2.5 × 2.5km is used in the process of calculating terrain correction. The calculation of the terrain effect is extended to the optimal distance 100km with average density of crustal rocks ρr=2.67g/cm3, and sea water density ρw=1.03 g/cm3. The obtained result of the terrain correction changes from -17.95 to +25.71 mGal in the whole region. By combining the above-mentioned terrain correction result with other data sources, the authors also have built a 2.5 × 2.5 km grid of complete Bouguer gravity anomaly data for East Vietnam Sea and adjacent areas.